The Influence of Experiential Marketing Strategy on Purchase Intention: A Literature Review - Cantika Yasmin Dwi Putranti; Harisatul Agustin; Geodita Woro Bramanti (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2024)
Purpose – This study aims to explore how experiential marketing influences consumers’ purchase intention toward slow fashion products at Sarinah Mall Indonesia. The research is motivated by the rising relevance of sustainable fashion consumption and Sarinah’s strategic repositioning to provide meaningful and memorable retail experiences. Methodology – A qualitative research design was employed to obtain an in-depth understanding of consumer perceptions and experiences. Data were collected through semi-structured interviews with visitors of slow fashion MSMEs at Sarinah Mall, selected using purposive sampling. The interviews were analyzed using thematic analysis to identify recurring patterns related to sensory experience, emotional engagement, cognitive reflections, behavioral responses, and social connection within the experiential marketing framework. Findings – The findings suggest that experiential marketing plays a substantial role in shaping consumer attitudes toward slow fashion. Participants reported that sensory and emotional experiences in Sarinah’s retail environment enhanced their appreciation of craftsmanship, sustainability values, and product authenticity. These experiential encounters strengthened personal relevance, stimulated curiosity, and encouraged deeper engagement with slow fashion brands, ultimately influencing their intention to purchase. The study highlights that meaningful interactions, rather than promotional messages alone, are central in fostering interest sustainably. Originality – This study contributes to the limited qualitative evidence on slow fashion adoption in Indonesia by integrating experiential marketing theory with consumer experience narratives. It provides nuanced insights into how consumers interpret slow fashion within a culturally embedded retail setting, offering a perspective rarely addressed in previous research dominated by quantitative approaches. Research limitations – The study is limited by its small sample size and focus on a single retail location, which may reduce the transferability of findings.